Perda auditiva induzida por ruído e saúde coletiva: revisão integrativa - Silva, Taysmara Xavier Santos (2023)
Occupational noise is present in most of the most varied work environments, and even today it is one of the main aggravating factors in the health of workers exposed to noise during their working hours. Objective: The study sought to identify and analyze the production of Brazilian scientific articles on noise-induced hearing loss in public health. Methods: An integrative review was carried out through an examining and selective reading of articles, and finally, recording of relevant information. The SCIELO, LILACS, VHL database was used as a research source, in the national scientific production, from 2012 to 2022, with the keywords: "noise-induced hearing loss OR noise-induced hearing loss AND Collective Health. Results and Discussion: Regarding the investigated population, we noticed that the articles selected professionals such as musicians, hospital laundry workers, urban transport drivers and collectors, in addition to all Brazilians who were notified with noise-induced hearing loss. daily occupational noise exposure routines. We found that the studies have similar purposes that deal with the theme of NIHL and workers' health, although it is necessary to carry out studies that deal with this relationship with speech therapy. Conclusion: Based on the results of the review, note it is essential to provide speech therapy monitoring within companies, through work to promote and prevent NIHL for occupational workers.